Analisis Yuridis Perkawinan Siri dalam Perspektif Kepastian Hukum - Sindi Fransiska (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the practice of unregistered marriage from the perspective of legal certainty and its implications for the legal status of wives and children. Normatively, unregistered marriage is declared valid if it meets the pillars and requirements as stipulated in the Compilation of Islamic Law, especially Article 14, but in the national legal system, this validity has not yet resulted in formal legal consequences without registration as required in Law Number 1 of 1974 concerning Marriage in conjunctionwith LawNumber 16 of 2019. By using normative legal research methods through statutory and conceptual approaches, this study found that the absence of registration weakens the legal position of the wife, especially in proving marital status, claims for maintenance and rights to joint property and has the potential to cause uncertainty in the administrative status and civil rights of children, even though the Constitutional Court Decision Number 46/PUU-VIII/2010 has expanded the civil relationship of children with their biological fathers as long as it can be proven scientifically or with other valid evidence. Therefore, from a legal perspective, the practice of unregistered marriages does not fully reflect the principle of legal certainty. Therefore, marriage registration must be viewed as a fundamental instrument for ensuring the protection of the civil rights of wives and children in the Indonesian legal system.